The Influence of IMC Implementation on the Brand Awareness of BLANJA.com - Ulfa Dinyah Fitri; Haris Herdiansyah (Jurnal Komunikasi Global, 2021)
Integrated marketing communication continues to be an important issue to create brand awareness of a product. This study aims to identify the influence of the integrated marketing communication elements implementation towards the brand awareness of BLANJA.com. The method used in this research is quantitative with an explanatory research approach. Data were collected through online questionnaires spread to the BLANJA.com customers.  There were 121 respondents involved in this study who were selected using the purposive sampling technique. The analysis technique used was multiple regression using SPSS 25.0.  This research found that advertising, sales promotion, public relation, and digital communication had a significant influence simultaneously towards the brand awareness of BLANJA.com, with the Coefficient of Determination is 80,7%. Further, digital communication had the most considerable impact partially on the brand awareness of BLANJA. Public relations and advertising also had significant influences partially towards the brand awareness of BLANJA.com. Komunikasi marketing terintegrasi masih menjadi topik yang penting dalam kaitannya dengan kesadaran merek dari suatu produk. Tujuan dari riset ini adalah untuk mengidentifikasi pengaruh implementasi elemen dari komunikasi marketing terintegrasi terhadap kesadaran merek dari Blanja.com. Metode yang digunakan adalah metode kuantitatif eksplanatif. Data responden didapat dengan menggunakan kuisioner terhadap pelanggan BLANJA.com. Sample yang terlibat sebanyak 121 responden yang dipilih dengan teknik purposive sampling. Teknik analisis data menggunakan regresi berganda yang diolah dengan SPSS 25.0. Hasil riset menunjukkan bahwa terdapat pengaruh yang signifikan dari iklan, promosi penjualan, hubungan masyarakat dan komunikasi digital terhadap kesadaran merek dari BLANJA.com dengan determinasi pengaruh sebesar 80,7%. Dari keempat elemen tersebut, yang paling berpengaruh terhadap kesadaran merek dari BLANJA.com adalah komunikasi digital, diikuti selanjutnya dengan humas, iklan, dan promosi penjualan.